Tindak Pidana Terorisme Dalam Perspektif Hukum Pidana Islam Dan Hukum Positif - Miski, Miski (Al-Mazaahib: Jurnal Perbandingan Hukum, 2021)
This article seeks to reveal the differences in the understanding, elements, and criminal sanctions of terrorism between Islamic criminal law and positive law that applies in Indonesia. This article is a qualitative research by utilizing literature as a source. The approach used is normative juridical to analyze data sourced from sources of Islamic law and Indonesian positive law. After being analyzed, the two sources are compared to find similarities and differences regarding criminal acts of terrorism from both perspectives. This article reveals that, in the discourse of Islamic criminal law, terrorism is equated with the concept of jarimah hirabah or acts of violence using weapons, creating fear in the victim, and resulting in the loss of other people's lives. Whereas in positive law, the element of criminal acts of terrorism is the use of violence that creates an atmosphere of terror and fear en masse. Criminal sanctions in Islamic criminal law are: killed and crucified, killed, cut off legs and arms crosswise and imprisoned. Whereas in positive law, the sanction is the death penalty, or imprisonment for a specified period of time.